Swidden, rubber and carbon: can REDD+ work for people and the environment in Montane Mainland Southeast Asia? - Fox, J.; Castella, J.C.; Ziegler, A.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Swidden (also called shifting cultivation) has long been the dominant farming system in Montane Mainland Southeast Asia (MMSEA). Today the ecological bounty of this region is threatened by the expansion of settled agriculture, including the proliferation of rubber plantations. In the current conception of REDD+, landscapes involving swidden qualify almost automatically for replacement by other land-use systems because swiddens are perceived to be degraded and inefficient with regard to carbon sequestration. However, swiddening in some cases may be carbon-neutral or even carbon positive, compared with some other types of land-use systems. In this paper we describe how agricultural policies and institutions have affected land use in the region over the last several decades and the impact these policies have had on the livelihoods of swiddeners and other smallholders. We also explore whether incentivizing transitions away from swiddening to the cultivation of rubber will directly or reliably produce carbon gains. We argue that because government policies affect how land is used, they also influence carbon emissions, farmer livelihoods, environmental services, and a host of other variables. A deeper and more systematic analysis of the multiple consequences of these policies is consequently necessary for the design of successful REDD+ policies in MMSEA, and other areas of the developing world. REDD + policies should be structured not so much to 'hold the forest boundary' but to influence the types of land-use changes that are occurring so that they support both sustainable livelihoods and environmental services, including (but not limited to) carbon.